Language and speech outcomes of children with hearing loss and additional disabilities: identifying the variables that influence performance at five years of age. (23rd March 2018) - Cupples, Linda; Ching, Teresa Y. C.; Button, Laura; Leigh, Greg; Marnane, Vivienne; Whitfield, Jessica; Gunnourie, Miriam; Martin, Louise
Abstract: Objective : This study examined language and speech outcomes in young children with hearing loss and additional disabilities. Design : Receptive and expressive language skills and speech output accuracy were evaluated using direct assessment and caregiver report. Results were analysed first for the entire participant cohort, and then to compare results for children with hearing aids (HAs) versus cochlear implants (CIs). Study sample : A population-based cohort of 146 five-year-old children with hearing loss and additional disabilities took part. Results : Across all participants, multiple regressions showed that better language outcomes were associated with milder hearing loss, use of oral communication, higher levels of cognitive ability and maternal education, and earlier device fitting. Speech output accuracy was associated with use of oral communication only. Average outcomes were similar for children with HAs versus CIs, but their associations with demographic variables differed. For HA users, results resembled those for the whole cohort. For CI users, only use of oral communication and higher cognitive ability levels were significantly associated with better language outcomes. Conclusions : The results underscore the importance of early device fitting for children with additional disabilities. Strong conclusions cannot be drawn for CI users given the small number of participants with complete data.